2011
DOI: 10.1007/s10584-011-0159-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in annual maximum snow depth and snowfall in Switzerland based on extreme value statistics

Abstract: Mountain snow cover is an important source of water and essential for winter tourism in Alpine countries. However, large amounts of snow can lead to destructive avalanches, floods, traffic interruptions or even the collapse of buildings. We use annual maximum snow depth and snowfall data from 25 stations (between 200 and 2,500 m) collected during the last 80 winters (1930/31 to 2009/2010) to highlight temporal trends of annual maximum snow depth and 3-day snowfall sum. The generalized extreme value (GEV) dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
2
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 41 publications
6
86
2
3
Order By: Relevance
“…In almost all northern Europe, a decrease in the winter total snowfall in twenty-first century was also suggested by 12 regional models under the SRES A1B scenario (Räisänen, 2015). The decreasing trend of snowfall across most areas of Northern Hemisphere may be due to the observed decrease of snow/rain ratio caused by the increase of air temperature (Marty and Blanchet, 2012;Krasting et al, 2013). Knowles et al (2006) also found that the ratio of snowfall water equivalent (SFE) to total precipitation (P ) became smaller in winter in the western United States during 1949States during -2004.…”
Section: Discussionmentioning
confidence: 70%
“…In almost all northern Europe, a decrease in the winter total snowfall in twenty-first century was also suggested by 12 regional models under the SRES A1B scenario (Räisänen, 2015). The decreasing trend of snowfall across most areas of Northern Hemisphere may be due to the observed decrease of snow/rain ratio caused by the increase of air temperature (Marty and Blanchet, 2012;Krasting et al, 2013). Knowles et al (2006) also found that the ratio of snowfall water equivalent (SFE) to total precipitation (P ) became smaller in winter in the western United States during 1949States during -2004.…”
Section: Discussionmentioning
confidence: 70%
“…The decreasing pattern for extreme snow fall rates is less clear than for extreme snow depth, except for low elevations where the influence of increasing temperatures is predominant (Marty and Blanchet, 2012). …”
Section: Observed Changes In Snow Covermentioning
confidence: 99%
“…The catastrophic effects of heavy snowfall range from avalanches and floods to road or rail damage. In extreme cases these events can even result in the weight-driven collapse of buildings or loss of human life (Marty and Blanchet, 2011). Also, mean snowfall conditions, such as the mean number of snowfall days in a given period, can be of high relevance for road management (e.g.…”
Section: Introductionmentioning
confidence: 99%